The Learning of DaF Subject during the Covid-19 Pandemic: The Perspective of the Teachers - Amalina Rachmi Fatina (PAROLE: Journal of Linguistics and Education, 2022)
Face-to-face learning has been shifted to online learning during the COVID-19 pandemic. Due to the online learning, learning support tools are needed to facilitate teaching and learning German. This study aims at describing the implementation of online German teaching and learning and the use of platforms to support German language learning in higher education based on pedagogy and technology aspects. The researcher talks about the experience of teaching German in the Deutsch I course through online learning. The German language that students learned was German at level A1. The research method used was qualitative research with a narrative approach. This method was chosen due to it was based on the researcher’s experience while teaching in the Deutsch I course. In this study, the data used were pictures and the results of students’ reflection with data collection techniques of observation, documentation, and questionnaire. The data were explained based on the pedagogical and technological aspects. In the pedagogical aspect, the implementation of German online learning was explained as well as the materials that were taught, whereas, in technological aspects, the applications used to support learning were explained namely WhatsApp, Zoom, Padlet, Quizlet, Kahoot, and Google Form. The results show that obstacles in online learning cannot be avoided. However, to overcome these obstacles, teachers can use other applications to provide and explain the material to students who are left behind, so the materials that have been determined in the curriculum can be delivered properly.